Dynamic contrast-enhanced magnetic resonance imaging of breast tumors at 3 and 7 T: a comparison - Gruber, Stephan; Pinker, Katja; Zaric, Olgica; Minarikova, Lenka; Chmelik, Marek; Baltzer, Pascal; Boubela, Roland N; Helbich, Thomas; Bogner, Wolfgang; Trattnig, Siegfried (Investigative radiology, 2014)
The objective of this study was to compare the image quality, contrast enhancement behavior, and diagnostic value of bilateral 3-dimensional dynamic contrast-enhanced breast magnetic resonance imaging (MRI), with high spatial and temporal resolution, at 3 and 7 T, in the same patient group. Twenty-four consecutive patients (mean [SD] age, 57 [17] years) were included in this prospective institutional review board-approved study. Written informed consent was obtained from all patients. T1-weighted 3-dimensional sequences (time-resolved angiography with stochastic trajectories) were optimized at 3 and 7 T, with high temporal (both 14 seconds) and spatial resolution (1.1 × 1.1 × 1.1 mm [3 T], 0.7 × 0.7 × 0.7 mm [7 T]): echo time/repetition time, 2.84/6.01 milliseconds (3 T) and 2.5/4.75 milliseconds (7 T); acquisition time, 9 minutes (3 T/7 T). Dotarem (gadoterate meglumine, Guerbet, Roissy CdG, France) contrast agent was injected intravenously as a bolus (0.2 mL/kg of body weight) after 3 baseline images. The images were rated according to breast imaging-reporting and data system by 2 radiologists in consensus. Signal-to-noise ratio and average enhancement ratios were measured quantitatively by means of region of interest analysis. In addition, B1 mapping was done in the same 5 healthy subjects at both field strengths. Twenty-eight enhancing lesions were detected in the 24 patients at both field strengths (16 malignant, 12 benign). At 7 T, higher contrast than that at 3 T and good image quality were achieved. With the high spatial isotropic resolution of 0.7 mm at 7 T, images with more detailed information could be acquired when compared with those acquired at 3 T. Sensitivity was 93.75% and 100%, at 3 and 7 T, respectively. Specificity was 91.67% at both field strengths. The signal-to-noise ratio at both field strengths was comparable, but at 7 T, the spatial resolution was 3.2-times higher than that at 3 T. A signal-to-noise ratio decrease toward prepectoral breast regions due to B1 inhomogeneities was observed at both field strengths but was stronger at 7 T (51%) than at 3 T (19%)(P = 0.0002). At 7 T, B1+ dropped by 20.7% and 32.8% in the prepectoral and lateral region of the breast in healthy subjects. Our comparison study shows that 7-T DCE-MRI provides simultaneous high temporal and spatial resolution that is significantly improved compared with lower field strengths, but further technical improvements are necessary to overcome B1 inhomogeneity problems at 7 T to fully unfold the potential of breast MRI at 7 T.